Aesthetics and Leadership: An Essay. Issue 7 (3rd October 2021) - Ramirez, Rafael
ABSTRACT: In 2016 the so-called "Coiffeurgate" scandal exploded in France. The socialist, and quite bald, President of the French Republic had been discovered paying (out of the public purse) 9, 985 euros per month for cutting his hair. Almost twelve thousand US dollars at today's exchange rate, that is, a cost of 400/day. Why would one make such an extravagant expense? Because of aesthetics. This essay reviews what aesthetics says about leaders and how they organize the perceptions of those they lead to try to become more attractive. This essay suggests that aesthetics operates at a deeper and more fundamental level than many other epistemological considerations; and that attending to how aesthetics operates informs much about how leadership works. The essay concludes that to counter the successful aesthetic projects of populist leaders, based on simplification, the challenge for opponents is to craft an aesthetics of clarity.